Broilers thermal comfort and performance utilizing two different wood-burning heating systems - Vigoderis, Ricardo Brauer (2018)
The objective of this study was to evaluate the thermal comfort and performance of broilers in their initial stage of development utilizing two different heating systems. The experiment was conducted in two sheds placed on a commercial farm. The heating systems were: indirect heating furnace and radiation heating drums. At the beginning of the heating phase the birds were confined in an area corresponding to 360 m² in shed 1 and 180 m² in shed 2, delimited by polyurethane curtains, allowing a density of 58.8 birds m-². The variables: dry bulb temperature (Tdb), relative humidity (RH%) and temperature and humidity index (THI) were calculated. Measurements were performed using continuous reading data loggers at 15-minute intervals throughout the experimental period, which was a complete productive cycle for males. Differences were detected in the environmental variables during the period evaluated, as well as differences in performance were found as a function of the two heating systems. The heating system of the furnace presented UR ranging from 47-59% in relation to the drum system (51-57%), besides providing a more constant temperature and providing a greater distribution of heating. On the other hand, the drum system provided greater weight gain in the animals.